AGLOMERATION OF Al2O3 NANOMETRIC AND SUBMICROMETRIC PARTICLES BY SPRAY DRYING FOR THEIR USE AS FEEDSTOCK IN THERMAL SPRAYING COATINGS - Cadavid, Edwin; Lopez, Esperanza; Vargas Galvis, Fabio (Revista Colombiana de Materiales, 2022)
This study focuses on optimizing the parameters of the spray-drying process for the agglomeration of both nanometric and submicrometric Al2O3 particles for their use as feedstock to manufacture thermally sprayed coatings. Initially, for an aqueous suspension with submicrometric alumina particles, d10 = 0.8 to d90 = 2.0 µm, named SA, was evaluated the effect of: i) The solids percentage in the aqueous suspension, ii) the feed flow rate and iii) the hot air rate used to evaporate the water in the suspension, on the agglomeration efficiency and the morphology of agglomerated obtained, utilizing a factorial experimental design with three factors and two levels. The agglomeration efficiency was calculated as the ratio between the weight percentage of granulated particles and the weight of solids in the sprayed slurry, while the morphology was analyzed by scanning electron spectroscopy SEM. The agglomeration results for the SA suspension indicate that the highest efficiency was achieved with a solid percentage in an aqueous suspension of 30 wt. % (10 vol.%), a feed rate of 3.1 ml/min and a hot air rate of 5.5 m3/min at a temperature of 220 °C, obtaining spherical agglomerates. Nevertheless, different morphologies of agglomerate were obtained based on the others experimental runs, such as hollow spheres. Subsequently, these parameters were replicated for a suspension of alumina nanoparticles, d50=80 nm, called NA, to obtain granules with a spherical morphology, composed of primary and secondary agglomerates whose size distributions correspond to d10 = 5 to d90 = 11 µm and d10 = 30 to d90 = 44 µm, respectively, with a total granulation efficiency of 80%, of which, 90% have a suitable range size to be used as raw material in the production of coatings by means of thermal spraying.